2021
DOI: 10.1177/0271678x211060741
|View full text |Cite
|
Sign up to set email alerts
|

D* from diffusion MRI reveals a correspondence between ventricular cerebrospinal fluid volume and flow in the ischemic rodent model

Abstract: Quantitative measurement of cerebrospinal fluid (CSF) flow and volume and longitudinal monitoring of CSF dynamics provide insights into the compensatory characteristics of post-stroke CSF. In this study, we compared the MRI pseudo-diffusion index ( D*) of live and sacrificed rat brains to confirm the effect of ventricular CSF flow on diffusion signals. We observed the relationship between the CSF peak velocities and D* through Monte Carlo (MC) simulations to further understand the source of D* contrast. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Nonetheless, recent studies have further explored the source of D* contrast in the CSF and shown a strong correlation between D* from diffusion-weighted signals and CSF peak velocity using Monte Carlo simulations. 11 Therefore measurements of D* may serve as a quantitative marker of fluid movement in the PVS and have the potential to be a useful non-invasive biomarker for derangement of PV function linked to pathological states of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent studies have further explored the source of D* contrast in the CSF and shown a strong correlation between D* from diffusion-weighted signals and CSF peak velocity using Monte Carlo simulations. 11 Therefore measurements of D* may serve as a quantitative marker of fluid movement in the PVS and have the potential to be a useful non-invasive biomarker for derangement of PV function linked to pathological states of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In disease conditions, activated SPAK has an important role in converting stress and cytokine inflammatory signaling, including TLR4 and NF-κB dependent activation, into NKCC1-mediated hyper-or pathological secretion of CSF (Robert et al, 2023). Other research in the field has also linked changes to these protein complexes to ChP CSF production dysregulation (Podvin et al, 2011;Jang et al, 2022). Further studies will be needed to investigate impact of increased phosphorylation states of SPAK and NKCC1 on ChP CSF regulation in ischemic stroke brains.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have correlated the diffusion coefficient measured by low b-value DWI to the velocity of the spins bulk flow. 71,[100][101][102][103][104][105][106][107][108][109][110] A low b-value diffusion gradient (5-150 s/mm 2 ) can be used to assess bulk flow velocities, 71,100,111 perfusion imaging, 112 and functional MRI. 101 Apparent diffusion coefficient (ADC) measurements using low b-values (short diffusion time) show restricted diffusion of CSF in choroid plexus cysts.…”
Section: Low B-value Dwimentioning
confidence: 99%
“…Additionally, it was demonstrated that the ADC may be used to evaluate both the pathological condition of the brain and the flow of CSF. 106 The phase shift in MRI diffusion-weighted images was used to measure the CSF flow velocity in the optic nerve in patients with normal tension glaucoma 107 and in patients with idiopathic intracranial hypertension (IIH). 108 In both patient groups, CSF flow velocity was lower than that of the healthy controls.…”
Section: Low B-value Dwimentioning
confidence: 99%
See 1 more Smart Citation